2018
DOI: 10.1017/s0144686x18000594
|View full text |Cite
|
Sign up to set email alerts
|

The role of the visual arts in the resilience of people living with dementia in care homes

Abstract: This study responds to a gap in the literature relating to the resilience of people living with dementia in care homes. We applied an ecopsychosocial framework of resilience, theorising that sources of resilience may be personal, social and structural. Visual arts enrichment activities were examined to see how they might provide opportunities for resilience. The data used for this study were qualitative and originated from people with dementia aged between 70 and 99 years old (N = 48) living in four care homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…This resulted in 53 studies being retained for full-text review, against the inclusion criteria. The final review included six papers that reported five interventions (27)(28)(29)(30)(31)(32). An overview of the studies and the interventions is provided below.…”
Section: Review Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…This resulted in 53 studies being retained for full-text review, against the inclusion criteria. The final review included six papers that reported five interventions (27)(28)(29)(30)(31)(32). An overview of the studies and the interventions is provided below.…”
Section: Review Findingsmentioning
confidence: 99%
“…The second study included in this review was conducted between 2013 and 2017 in the UK (29). This study aimed to evaluate the impact of visual arts enrichment activities (VAEA) on opportunities for the resilience of people with dementia.…”
Section: Visual Arts Enrichment Activitiesmentioning
confidence: 99%
See 3 more Smart Citations